Harnessing cellular immunity for next-generation vaccines against respiratory viruses: mechanisms, platforms, and optimization strategies - Chen, Keda; Hu, Jutao; Li, Jiaxuan; Wu, Guangshang; Tie, Xiaotian; Wu, Hao; Li, Hongyu; Li, Jianhua; Zhang, Yanjun (Frontiers in Immunology, 2025)
Respiratory tract infections, such as influenza, respiratory syncytial virus (RSV) infection, and COVID-19, remain a persistent threat to global public health due to their high transmissibility and disease burden. Vaccination, as a key preventive strategy, not only reduces the risk of infection but also blocks transmission by activating adaptive immunity. While traditional vaccine evaluations have primarily focused on humoral immunity, growing evidence highlights the critical role of T lymphocyte-mediated cellular immunity in clearing virus-infected cells, establishing long-term immune memory, and responding to viral mutations. This review systematically summarizes the cellular immune responses induced by vaccines against respiratory tract infections and their correlation with protective efficacy. It also outlines evaluation methodologies such as flow cytometry, providing a theoretical foundation for optimizing vaccine design and assessment, and advancing the development of effective, broad-spectrum vaccines.